A two-degree-of-freedom linear encoder with a mosaic scale grating. (9th May 2011) - Kimura, Akihide; Hosono, Koji; Kim, WooJae; Shimizu, Yuki; Gao, Wei; Zeng, Lijiang
A new optical two-degree-of-freedom (2-DOF) linear encoder with a mosaic scale grating is proposed to expand the measurement range along the in-plane direction of the grating. The 2-DOF linear encoder has the ability to measure the in-plane displacement along the axis of the scale grating (X-axis) and the out-of-plane displacement perpendicular to the scale grating plane (Z-axis). The measurement range of the optical linear encoder along the X-axis, which is determined by the length of the scale grating, is expanded by using a mosaic scale grating with multiple scale gratings aligned along the X-axis. A new optical configuration of the sensor head, which projecting multiple light probes onto the mosaic scale grating, is presented. The 2-DOF displacements can be obtained accurately from the probe which is not on the gaps between scale gratings. The feasibility of the 2-DOF linear encoder with the multi-probe configuration has been verified by experimental results. The X-and Z-directional resolutions were about 5 nm and 1 nm, respectively. The peak to valley amplitude of the non-linear component was within ±50 nm in the measurement error of the X-directional sensor output, which was obtained by the stitching outputs from the multiple light probes.